Flexible Functional Forms and Regularity: Assessing the Competitive Relationship between Truck and Rail Transportation - Westbrook, M. Daniel; Buckley, Patricia A. (The Review of Economics and Statistics, 1990)
M. Daniel Westbrook, Patricia A. Buckley, Flexible Functional Forms and Regularity: Assessing the Competitive Relationship between Truck and Rail Transportation, The Review of Economics and Statistics, Vol. 72, No. 4 (Nov., 1990), pp. 623-630